Comparison of Typhidot IgM test and blood culture in children with clinically compatible enteric fever - Garg, Sandeep; Sankhe, Ajay; Joshi, Anuradha; Mehta, Samrat (International Journal of Contemporary Pediatrics, 2018)
Background: The often-non-specific presentation of typhoid fever makes clinical diagnosis difficult. The blood culture is time consuming, affected by often given prior antibiotics and has low sensitivity (60%). Typhidot IgM gives quick results in early stage of disease. Pediatric data are scarce. So, we studied and compare Typhidot IgM test and blood culture in children with clinically compatible enteric fever. Methods: This was retrospective observational study done in Department of Pediatrics from the 1st October, 2017 to 30 September, 2018. 42 children with clinically compatible enteric fever (aged 6 months to 18 years); with either typhidot IgM or blood culture positive for Salmonella species were sampled and analyzed. Results: Typhidot IgM test had sensitivity of 92.7% (N = 39/42) compared to blood culture with sensitivity of 79.4% (N = 27/34). 2 out of 3 typhidot negative cases were S. Paratyphi positive in blood culture. Typhidot IgM had positive predictive value = 97.4% due to 1 false positive case. 19 (79.2%) out of 24 blood culture positive patients had not received any antibiotic prior test, 3 (60 %) out of 5 blood culture negative patients had received antibiotics. Conclusions: Typhidot IgM is a highly sensitive quick diagnostic tool for diagnosing enteric fever in children with sensitivity of 92.3% and PPV of 97.4% compared to blood culture (sensitivity= 79.4%). It is more sensitive to diagnose S. typhi enteric fever (sensitivity= 97.3%) then S. paratyphi (sensitivity= 50%). Antibiotic administration prior to blood culture testing reduces its positivity rate but not significantly statistically. Larger studies are needed to change the current recommendations on typhidot IgM.